Nano-TiO2 Adsorbed Decabromodiphenyl Ethane and Changed Its Bioavailability, Biotransformation and Biotoxicity in Zebrafish Embryos/Larvae - Wang, Xiulin; Sun, Yumiao; Fu, Mengru; Chen, Pengyu; Wang, Qiangwei; Hua, Jianghuan; Fu, Kaiyu; Zhang, Wei; Zhu, Lifei; Yang, Lihua; Zhou, Bingsheng (Frontiers in Environmental Science, 2022)
Decabromodiphenyl ethane (DBDPE), a novel brominated flame retardant, exhibits similar environmental behavior, thyroid disrupting effect, and neurotoxicity to decabromodiphenyl ether. This study further evaluated the behavior of DBDPE in aqueous environments along with the bioavailability and toxicity of DBDPE in aquatic organisms in the presence of TiO2 nanoparticles (n-TiO2). When co-existing in an aqueous environment, DBDPE was adsorbed by n-TiO2, potentially facilitating the sedimentation of DBDPE from the aqueous phase. Co-exposure to DBDPE and n-TiO2 significantly increased the uptake of DBDPE by zebrafish (Danio rerio) embryos and altered the composition of metabolites in zebrafish larvae compared to zebrafish exposed to DBDPE alone. The DBDPE-induced increases in heart rate, tail bending frequency, average speed under dark/light stimulation, and thyroid hormone levels in zebrafish embryos/larvae were further enhanced in the presence of n-TiO2. Overall, the results demonstrate that n-TiO2 affected the behavior of DBDPE in the aqueous phase and increased the bioavailability and biotoxicity of DBDPE in zebrafish embryos/larvae. These results provide novel information for assessing the potential ecological and health risks of DBDPE.